Experimental Study in Compressive Strength with Respect to Different Thicknesses of Composite Material - Katimon, Mohd Nizam; Nur Akmal Hakim, (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Carbon Fiber is a polymer that is occasionally referred to as graphite fiber. It is a material that is both highly durable and lightweight. Carbon fiber is five times as strong and twice as rigid as steel. Carbon fibers have a low weight-to-strength ratio, excellent chemical resistance, a low temperature of overheating, and limited thermal expansion. Carbon fiber's rigidity, lightness, and stiffness have made it a possible alternative for steel in numerous applications. This study aimed to differentiate the compressive strength result between two-layer and three-layers of carbon fiber tube specimen. A total of six samples of carbon fiber tubes consist of three specimens for two-layer carbon fiber tubes and three specimens for three-layer carbon fiber tubes. The thickness difference between these two samples was only 1.0 mm, which is 1.5 mm for two layers and 2.5 mm for three layers. This study carried out a compression test using a universal testing machine with a maximum load of 10kN to measure the maximum force to break a specimen. The optical microscope was used to identify the failure of the specimen. As a result, it shows that two-layer and three-layer were able to withstand up to a maximum load of 10 kN.